a(p(x1)) → p(a(A(x1)))
a(A(x1)) → A(a(x1))
p(A(A(x1))) → a(p(x1))
↳ QTRS
↳ DependencyPairsProof
↳ QTRS Reverse
↳ QTRS Reverse
a(p(x1)) → p(a(A(x1)))
a(A(x1)) → A(a(x1))
p(A(A(x1))) → a(p(x1))
A1(p(x1)) → A1(A(x1))
P(A(A(x1))) → P(x1)
A1(p(x1)) → P(a(A(x1)))
P(A(A(x1))) → A1(p(x1))
A1(A(x1)) → A1(x1)
a(p(x1)) → p(a(A(x1)))
a(A(x1)) → A(a(x1))
p(A(A(x1))) → a(p(x1))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QTRS Reverse
↳ QTRS Reverse
A1(p(x1)) → A1(A(x1))
P(A(A(x1))) → P(x1)
A1(p(x1)) → P(a(A(x1)))
P(A(A(x1))) → A1(p(x1))
A1(A(x1)) → A1(x1)
a(p(x1)) → p(a(A(x1)))
a(A(x1)) → A(a(x1))
p(A(A(x1))) → a(p(x1))
A1(p(x1)) → A1(A(x1))
POL(A(x1)) = x1
POL(A1(x1)) = 2·x1
POL(P(x1)) = 2 + 2·x1
POL(a(x1)) = x1
POL(p(x1)) = 1 + x1
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ QDPOrderProof
↳ QTRS Reverse
↳ QTRS Reverse
P(A(A(x1))) → P(x1)
A1(p(x1)) → P(a(A(x1)))
A1(A(x1)) → A1(x1)
P(A(A(x1))) → A1(p(x1))
a(p(x1)) → p(a(A(x1)))
a(A(x1)) → A(a(x1))
p(A(A(x1))) → a(p(x1))
The following pairs can be oriented strictly and are deleted.
The remaining pairs can at least be oriented weakly.
A1(A(x1)) → A1(x1)
Used ordering: Polynomial interpretation [25,35]:
P(A(A(x1))) → P(x1)
A1(p(x1)) → P(a(A(x1)))
P(A(A(x1))) → A1(p(x1))
The value of delta used in the strict ordering is 2.
POL(P(x1)) = 0
POL(A1(x1)) = x_1
POL(a(x1)) = (4)x_1
POL(A(x1)) = 2 + (4)x_1
POL(p(x1)) = 0
a(A(x1)) → A(a(x1))
a(p(x1)) → p(a(A(x1)))
p(A(A(x1))) → a(p(x1))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
↳ QTRS Reverse
P(A(A(x1))) → P(x1)
A1(p(x1)) → P(a(A(x1)))
P(A(A(x1))) → A1(p(x1))
a(p(x1)) → p(a(A(x1)))
a(A(x1)) → A(a(x1))
p(A(A(x1))) → a(p(x1))
A1(p(x0)) → P(A(a(x0)))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS Reverse
↳ QTRS Reverse
A1(p(x0)) → P(A(a(x0)))
P(A(A(x1))) → P(x1)
P(A(A(x1))) → A1(p(x1))
a(p(x1)) → p(a(A(x1)))
a(A(x1)) → A(a(x1))
p(A(A(x1))) → a(p(x1))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
a(p(x1)) → p(a(A(x1)))
a(A(x1)) → A(a(x1))
p(A(A(x1))) → a(p(x1))
A1(p(x0)) → P(A(a(x0)))
P(A(A(x1))) → P(x1)
P(A(A(x1))) → A1(p(x1))
a(p(x1)) → p(a(A(x1)))
a(A(x1)) → A(a(x1))
p(A(A(x1))) → a(p(x1))
A1(p(x0)) → P(A(a(x0)))
P(A(A(x1))) → P(x1)
P(A(A(x1))) → A1(p(x1))
p(a(x)) → A(a(p(x)))
A(a(x)) → a(A(x))
A(A(p(x))) → p(a(x))
p(A1(x)) → a(A(P(x)))
A(A(P(x))) → P(x)
A(A(P(x))) → p(A1(x))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ RRRPoloQTRSProof
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
p(a(x)) → A(a(p(x)))
A(a(x)) → a(A(x))
A(A(p(x))) → p(a(x))
p(A1(x)) → a(A(P(x)))
A(A(P(x))) → P(x)
A(A(P(x))) → p(A1(x))
p(a(x)) → A(a(p(x)))
A(a(x)) → a(A(x))
A(A(p(x))) → p(a(x))
p(A1(x)) → a(A(P(x)))
A(A(P(x))) → P(x)
A(A(P(x))) → p(A1(x))
a(p(x)) → p(a(A(x)))
a(A(x)) → A(a(x))
p(A(A(x))) → a(p(x))
A1(p(x)) → P(A(a(x)))
P(A(A(x))) → P(x)
P(A(A(x))) → A1(p(x))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ RRRPoloQTRSProof
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
a(p(x)) → p(a(A(x)))
a(A(x)) → A(a(x))
p(A(A(x))) → a(p(x))
A1(p(x)) → P(A(a(x)))
P(A(A(x))) → P(x)
P(A(A(x))) → A1(p(x))
p(a(x)) → A(a(p(x)))
A(a(x)) → a(A(x))
A(A(p(x))) → p(a(x))
p(A1(x)) → a(A(P(x)))
A(A(P(x))) → P(x)
A(A(P(x))) → p(A1(x))
Used ordering:
A(A(P(x))) → P(x)
POL(A(x1)) = 2 + x1
POL(A1(x1)) = 2 + x1
POL(P(x1)) = 2·x1
POL(a(x1)) = 2 + x1
POL(p(x1)) = 2·x1
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ RRRPoloQTRSProof
↳ QTRS
↳ DependencyPairsProof
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
p(a(x)) → A(a(p(x)))
A(a(x)) → a(A(x))
A(A(p(x))) → p(a(x))
p(A1(x)) → a(A(P(x)))
A(A(P(x))) → p(A1(x))
P1(A1(x)) → A2(P(x))
A2(a(x)) → A2(x)
P1(a(x)) → P1(x)
A2(A(P(x))) → P1(A1(x))
A2(A(p(x))) → P1(a(x))
P1(a(x)) → A2(a(p(x)))
p(a(x)) → A(a(p(x)))
A(a(x)) → a(A(x))
A(A(p(x))) → p(a(x))
p(A1(x)) → a(A(P(x)))
A(A(P(x))) → p(A1(x))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ RRRPoloQTRSProof
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
P1(A1(x)) → A2(P(x))
A2(a(x)) → A2(x)
P1(a(x)) → P1(x)
A2(A(P(x))) → P1(A1(x))
A2(A(p(x))) → P1(a(x))
P1(a(x)) → A2(a(p(x)))
p(a(x)) → A(a(p(x)))
A(a(x)) → a(A(x))
A(A(p(x))) → p(a(x))
p(A1(x)) → a(A(P(x)))
A(A(P(x))) → p(A1(x))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ RRRPoloQTRSProof
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
A2(a(x)) → A2(x)
P1(a(x)) → P1(x)
P1(a(x)) → A2(a(p(x)))
A2(A(p(x))) → P1(a(x))
p(a(x)) → A(a(p(x)))
A(a(x)) → a(A(x))
A(A(p(x))) → p(a(x))
p(A1(x)) → a(A(P(x)))
A(A(P(x))) → p(A1(x))
A2(a(x)) → A2(x)
P1(a(x)) → P1(x)
POL(A(x1)) = 1 + x1
POL(A1(x1)) = 1 + x1
POL(A2(x1)) = 2 + x1
POL(P(x1)) = 2·x1
POL(P1(x1)) = 1 + 2·x1
POL(a(x1)) = 1 + x1
POL(p(x1)) = 2·x1
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ RRRPoloQTRSProof
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
A2(A(p(x))) → P1(a(x))
P1(a(x)) → A2(a(p(x)))
p(a(x)) → A(a(p(x)))
A(a(x)) → a(A(x))
A(A(p(x))) → p(a(x))
p(A1(x)) → a(A(P(x)))
A(A(P(x))) → p(A1(x))
p(a(x)) → A(a(p(x)))
A(a(x)) → a(A(x))
A(A(p(x))) → p(a(x))
p(A1(x)) → a(A(P(x)))
A(A(P(x))) → P(x)
A(A(P(x))) → p(A1(x))
a(p(x)) → p(a(A(x)))
a(A(x)) → A(a(x))
p(A(A(x))) → a(p(x))
A1(p(x)) → P(A(a(x)))
P(A(A(x))) → P(x)
P(A(A(x))) → A1(p(x))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ RRRPoloQTRSProof
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
a(p(x)) → p(a(A(x)))
a(A(x)) → A(a(x))
p(A(A(x))) → a(p(x))
A1(p(x)) → P(A(a(x)))
P(A(A(x))) → P(x)
P(A(A(x))) → A1(p(x))
a(p(x1)) → p(a(A(x1)))
a(A(x1)) → A(a(x1))
p(A(A(x1))) → a(p(x1))
p(a(x)) → A(a(p(x)))
A(a(x)) → a(A(x))
A(A(p(x))) → p(a(x))
↳ QTRS
↳ DependencyPairsProof
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
p(a(x)) → A(a(p(x)))
A(a(x)) → a(A(x))
A(A(p(x))) → p(a(x))
a(p(x1)) → p(a(A(x1)))
a(A(x1)) → A(a(x1))
p(A(A(x1))) → a(p(x1))
p(a(x)) → A(a(p(x)))
A(a(x)) → a(A(x))
A(A(p(x))) → p(a(x))
↳ QTRS
↳ DependencyPairsProof
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS
p(a(x)) → A(a(p(x)))
A(a(x)) → a(A(x))
A(A(p(x))) → p(a(x))